1995
DOI: 10.1021/j100019a070
|View full text |Cite
|
Sign up to set email alerts
|

Time- and Space-Resolved Studies of the Physics and Chemistry of Liquid Water near a Biologically Relevant Interface

Abstract: In this paper, a new method for analyzing certain physical and chemical properties of liquid water near surfaces is described. "Probe" molecules are dissolved in the water system and are excited by a short laser pulse. The ability of the probe to undergo a fast nonradiative process depends on a reorientational relaxation time of the water solvent, which may become orders of magnitude slower for water near a surface. Using timeresolved methods and a sufficiently fast probe, one can observe a direct dynamic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
114
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 3 publications
9
114
0
Order By: Relevance
“…2(e). The decay time (τ) ranged from 0.25 to 14.2 ns, depending on the nature of the solvent ( 14,37 In the micellar systems, on the other hand, the fluorescence decayed faster for the micelles with a larger w 0 value. Furthermore, it is worth noting that the decay profile cannot be analyzed by a single exponential function, but by a double-or triple-exponential function as judged from the weighted residuals, the chai-squared (χ 2 ) and Durbin-Watson (D.W.) parameters for the fitting; the results are summarized in Table 2.…”
Section: Fluorescence Dynamics Of Ans In Reverse Aot Micelles and Itsmentioning
confidence: 99%
See 3 more Smart Citations
“…2(e). The decay time (τ) ranged from 0.25 to 14.2 ns, depending on the nature of the solvent ( 14,37 In the micellar systems, on the other hand, the fluorescence decayed faster for the micelles with a larger w 0 value. Furthermore, it is worth noting that the decay profile cannot be analyzed by a single exponential function, but by a double-or triple-exponential function as judged from the weighted residuals, the chai-squared (χ 2 ) and Durbin-Watson (D.W.) parameters for the fitting; the results are summarized in Table 2.…”
Section: Fluorescence Dynamics Of Ans In Reverse Aot Micelles and Itsmentioning
confidence: 99%
“…7,[13][14][15][16][17][18][19][20][21] As an example, Cho et al reported that ANS in reverse AOT micelles exhibited a double exponential decay: short component=0.3 -0.6 ns and long component=2.6 -5.1 ns at w 0 =4 -33.…”
Section: Fluorescence Dynamics Of Ans In Reverse Aot Micelles and Itsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Thus, they have been extensively studied as models of confined water in macromolecules, or as models of biologically relevant interfaces. 13 We found that the UTL has provided further information on the corrective behaviors of such inhomogeneous environments where several kinds of molecules interact with each other. 14,15 The second and third sections present the development of new instruments that we have newly developed.…”
mentioning
confidence: 75%